Battery Powered By The Pv System Using Multilevel Inverter At 5 Level To Maximise The Efficiency - et. al., R. Saranraj, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The multilevel converters has been recently considered as emerging alternatives in low and medium range power applications instead of solid state converting units. Multilevel inverters i.e. voltage source inverter has been establish with special features as compared to their conventional devices. One of the main features is that filter requirement has been reduced by getting the staircase output waveforms of low harmonics distortion from the various level DC sources. This makes multilevel inverter technology attractive for battery powered by the PV applications. In this Paper, discuss on operation of cascaded PV panels with MLI and its efficiency.